Ammonia decomposition catalysis using lithium–calcium imide - Makepeace, J; Hunter, H; Wood, T; Smith, R; Murray, C; David, W (Royal Society of Chemistry, 2015)
© 2016 The Royal Society of Chemistry.Lithium-calcium imide is explored as a catalyst for the decomposition of ammonia. It shows the highest ammonia decomposition activity yet reported for a pure light metal amide or imide, comparable to lithium imide-amide at high temperature, with superior conversion observed at lower temperatures. Importantly, the post-reaction mass recovery of lithium-calcium imide is almost complete, indicating that it may be easier to contain than the other amide-imide catalysts reported to date. The basis of this improved recovery is that the catalyst is, at least partially, solid across the temperature range studied under ammonia flow. However, lithium-calcium imide itself is only stable at low and high temperatures under ammonia, with in situ powder diffraction showing the decomposition of the catalyst to lithium amide-imide and calcium imide at intermediate temperatures of 200-460 °C.